Nurses' Ethical Challenges During Caring for COVID-19 Patients: Literature Study - Iis Haryati; Yanny Trisyani; Aan Nuraeni (Jurnal Berita Ilmu Keperawatan, 2022)
The COVID-19 pandemic has had many impacts on health services. As the most health workers who stand on the front lines, nurses have faced many ethical challenges when treating patients with COVID-19. The ethical challenge of nurses is basically due to the gap between nursing practice and nursing goals. This study aims to identify empirical evidence related to nurses' ethical challenges when caring for COVID-19 patients. This research method uses a literature study analyzing articles from four reputable databases such as Pubmed, Proquest, CINAHL, Science Direct, and one search engine Google Scholar with publication years between 2020 - 2021. The keywords used are 'COVID-19', 'critical care nursing', 'caring', 'ethical challenges', 'ethical issues', and 'ethical dilemmas' with the help of boolean operators 'OR' and 'AND', articles were selected in stages using PRISMA. From the results of 854 articles, only 7 articles were identified that met the inclusion and exclusion criteria. The Article review result found three themes related to the ethical challenges that occurred, namely the ethical challenges in the nursing care process, ethical challenges in nursing professionals, and ethical challenges in health interprofessional relationships. Ethical challenges cause nurses' discomfort at work, and can even cause job stress. Regarding these results, nurses need to get support to overcome ethical dilemmas that occur through the provision of resources according to needs, preparation of SOPs regarding the roles and duties of nurses, as well as increasing knowledge related to the care of COVID-19 patients.